Paenibacillus terrae AY-38 resistance against Botrytis cinerea in Solanum lycopersicum L. plants through defence hormones regulation - Ah-Young Kim; Raheem Shahzad; Sang-Mo Kang; Abdul Latif Khan; Seok-min Lee; Yeon-Gyeong Park; Won-Hee Lee; In-Jung Lee (Journal of Plant Interactions, 2017)
This study aims to investigate the role of Paenibacillus terrae AY-38 to produce bioactive metabolites and to counteract pathogenic infections caused by B. cinerea. The pure culture of P. terrae (AY-38) showed the secretion of significant amount of IAA (indole-3-acetic acid) (109.57 ± 3.2 µg mL−1). The AY-38 strain also produced siderophore and glucanase, while in the in vitro test, it showed significant antagonism to Botrytis cinerea. In the in vivo plant experiment, the sole application of AY-38 significantly improved plant growth (plant height and leaf area), while in B. cinerea infected plants, AY-38 inoculation not only decreased the disease incidence on leaves and fruits but also reprogramed the plants for higher growth. AY-38 treatments promoted and rescued plant growth by modulating the defence responses of endogenous hormones, such as jasmonic and salicylic acids. Our findings concluded that P. terrae possesses great potential as a possible biocontrol agent against B. cinerea-induced pathogenic infections.